ANALISIS NILAI CBR DESAIN TANAH DASAR DENGAN DYNAMIC CONE PENETROMETER PADA PEKERJAAN LONGSORAN STA 1+600, RUAS 041 RUAS JALAN NASIONAL PADANGSIDIMPUAN – BATAS SUMBAR - Muda, Anwar (Inersia: Jurnal Teknik Sipil, 2022)
The background of the research is that landslides often occur at the location of sta 1+600, section 041 or to be precise in Purba Lamo Village, Lembah Sorik Marapi District Mandailing Natal Regency, North Sumatra,  and efforts have been made with emergency handling with coconut stem stakes and assisted with sand back. slides still occur. In 2021, landslides will be handled at this location, but the avalanches are not handled, but instead a road route is diverted with the aim of avoiding and keeping traffic away from the landslide point location. Meanwhile, the work of diverting the route of this road is the same as making a new road, where every new road construction requires data on the carrying capacity of the subgrade by testing the CBR value. To get the CBR value of the subgrade in this study, the Dynamic Cone Penetrometer (DCP) test was carried out.The results of the DCP test showed that the CBR value of the subgrade design was 1.80%, so that this soil was classified as a soil that had poor subgrade bearing capacity or organic soil.